Allocation of photoassimilated carbon of radiata pine (Pinus radiata) seedlings as affected by soil water stress. Issue 1 (2nd January 2021) - Jeong, J.; Bolan, N. S.; Kim, C.
ABSTRACT: This study was carried out to determine the carbon (C) allocation of tree components following water stress in radiata pine ( Pinus radiata ) seedlings. The seedlings were exposed to various water contents (low, moderate and high soil water content) for 30 days and labelled with 14 CO2 gas for six hours on the 31st day. Biomass in all seedling components (foliage, stems and roots) was significantly higher in the moderate soil water content treatment than in the low soil water content treatment, while seedling biomass did not significantly differ between the moderate soil water and high soil water content treatments. The shoot/root ratio of seedlings decreased when soil water content decreased. The C concentrations of radiata pine seedlings were not affected by the soil water content, whereas the soil water stress-induced difference in the C allocation of seedlings was attributed to differences in seedling biomass. The translocation of pulse-labelled 14 C from the foliage to the roots was enhanced by low soil water content. The distribution of 14 C was highest in foliage, followed by roots, stems and soil. The results indicate that soil water content was one of the primary factors influencing biomass allocation in the early growth of radiata pine seedlings.